Does self-recognition of one's own fall recruit genuine bodily crisis-related brain activity? - Yoshiaki Kikuchi (Japanese Society of Physical Fitness and Sports Medicine, 2015)
While bipedalism is a fundamental evolutionary adaptation that is essential for the development of the human brain, the erect body is always an inch or two away from falling. Although the neural substrate underlying automatic detection of one's own body instability is an important consideration, there have thus far been few functional neuroimaging studies due to the restrictions placed on participants' movements. Here, we used functional magnetic resonance imaging to investigate the neural substrate underlying whole body instability, based on a self-recognition paradigm that uses video stimuli consisting of one's own and others' whole bodies, depicted in both stable and unstable states. Analyses revealed significant activity in the brain regions that should be activated during genuine unstable body (physical) conditions: the right parieto-insular vestibular cortex, inferior frontal junction, posterior insula and parabrachial nucleus. We argue that these right-lateralized cortical and brainstem regions mediate vestibular information processing for detection of vestibular anomalies, defensive motor responding in which the necessary motor responses are automatically prepared/simulated to protect one's body, and sympathetic activity as an alarm response during whole body instability.